Higher education and economic innovation, a comparison of European countries - Cecile Hoareau; Jo Ritzen; Gabriele Marconi (IZA Journal of European Labor Studies, 2013)
This paper compares higher education policies across thirty two European countries, using the contribution to economic innovation as a benchmark for the comparison. We suggest that an increase in university autonomy and public funding, that we qualify as 'empowerment', positively affects the research and education performance of universities, and more importantly the innovation potential of countries. We subsequently formulate policy related recommendations for Europe.
Keywords: 330